2011
DOI: 10.4191/kcers.2011.48.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Metal (Pt, Pd and Fe)-graphene Composites

Abstract: In this study, we prepared graphene by using the modified Hummers-Offeman method and then introduced the metals (Pt, Pd and Fe) for dispersion on the surface of the graphene for synthesis of metal-graphene composites. The characterization of the prepared graphene and metal-graphene composites was performed by X-ray diffraction (XRD), scanning electron microscopy (SEM) with energy dispersive X-ray (EDX) analysis and transmission electron microscopy (TEM). According to the results, it can be observed that the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 20 publications
1
24
0
2
Order By: Relevance
“…The preparation method and the reaction conditions could strongly affect the nature and the number of layers of the GR. Chen et al and Subrahmanyam et al prepared GR from GO, and they also found wrinkled nature of GR layers as we have shown in Fig. .…”
Section: Resultssupporting
confidence: 68%
“…The preparation method and the reaction conditions could strongly affect the nature and the number of layers of the GR. Chen et al and Subrahmanyam et al prepared GR from GO, and they also found wrinkled nature of GR layers as we have shown in Fig. .…”
Section: Resultssupporting
confidence: 68%
“…Oxidized graphite was first synthesized using modified version of previously reported methods [21,22]. In brief, 10 g of cleaned graphite powder (<20 m, Sigma-Aldrich) was slowly mixed with 230 mL of cold concentrated H 2 SO 4 (98%, Duksan) in an ice bath, to keep the temperature below 10 • C, with stirring.…”
Section: Photocatalystsmentioning
confidence: 99%
“…6 mL ammonium hydroxide (NH 4 OH, 28%, DaeJung Chemicals &Metal Co., Ltd, Korea) was added to it and the mixture was stirred till it dissolved completely to form Cd(NH 3 ) 4 2+ solution. 0.5 g graphene oxide which prepared by a Hummers-Offeman method in our previous works [14][15][16] was added into Na 2 SeSO 3 solution and Cd(NH 3 ) 4 2+ solution under stirring to allow formation of hydrogen bands between CdSe nanocrystals and graphene oxide. After a hydrothermal reaction at 80 ℃ for 5 h, graphene oxide was reduced to graphene nanosheet and CdSe compounds naturally grew on its surface to generate a graphene-CdSe composite.…”
Section: Preparation Of Graphene-cdse Compositementioning
confidence: 99%